DEVELOPMENT OF TiCoO2 SEMICONDUCTOR FILM - M. N. Indro; A. Kartono; M. Kurniati; B. Safitri (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
DEVELOPMENT OF TiCoO2 SEMICONDUCTOR FILM. Good quality of TiO2 and TiCoO2 films may be developed using Metal Organic Chemical Vapor Deposition (MOCVD) technique at the temperature around 450 oC on silicon substrate. The X-Rays Diffractometer (XRD) investigation on their crystals structure has shown that the samples resulted through this technique are almost as homogenously single crystals. Observation using Scanning Electron Microscope (SEM) technique on their surfaces has shown that the films have a constant thickness around 0.7mm and smooth surfaces. Further investigation on their magnetic behavior results in magnetic hysteresis at the coercive field around 80-150 Oe, with the largest remanent magnetization about 150-250 emu/cm3.